Ensinar e aprender as fases da Lua e os eclipses numa perspectiva construtivista - Mano, Amanda de Mattos Pereira (Editora Oficina Universitária, 2022)
Living the experience of reading the book Teaching and Learning as Phases of the Moon and Eclipses in a Constructivist Perspective, by the author Amanda de Mattos Pereira Mano, provided me with the disequilibrium typical of the restlessness of those who question themselves in the constitution of the professional practice lived in a context of Higher Education, in a space for teacher training, but also in revisiting experiences when acting in pedagogical coordination in Basic Education with the Final Years of Elementary Education and in the Youth and Adult Education modality. And this concern makes the book an important reading for teachers in initial and/or continuing training, especially for the invitation to reflect on the knowledge constructed by students as well as the hypotheses elaborated for the different processes of learning constitution.